2018
DOI: 10.1093/nar/gky1197
|View full text |Cite|
|
Sign up to set email alerts
|

An ultra-high affinity ligand of HIV-1 TAR reveals the RNA structure recognized by P-TEFb

Abstract: The HIV-1 trans-activator protein Tat binds the trans-activation response element (TAR) to facilitate recruitment of the super elongation complex (SEC) to enhance transcription of the integrated pro-viral genome. The Tat–TAR interaction is critical for viral replication and the emergence of the virus from the latent state, therefore, inhibiting this interaction has long been pursued to discover new anti-viral or latency reversal agents. However, discovering active compounds that directly target RNA with high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 56 publications
2
82
0
Order By: Relevance
“…5, C and D) to produce a number of cyclic peptides (82,137,138) that culminated recently in an "ultrahigh affinity" cyclic peptidomimetic. This inhibitor, JB181, binds HIV-1 TAR with an unprecedented K D (63). NMR solution analysis revealed that JB181 recognizes TAR in the s1b major groove and bulge (Fig.…”
Section: Tar Recognition By Structure-based Design Of Cyclic Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…5, C and D) to produce a number of cyclic peptides (82,137,138) that culminated recently in an "ultrahigh affinity" cyclic peptidomimetic. This inhibitor, JB181, binds HIV-1 TAR with an unprecedented K D (63). NMR solution analysis revealed that JB181 recognizes TAR in the s1b major groove and bulge (Fig.…”
Section: Tar Recognition By Structure-based Design Of Cyclic Peptidesmentioning
confidence: 99%
“…H, close-up view of HIV-1 TAR recognition in the central UCU bulge by TBP6.7. Arg-47 engages TAR at the ASM, similar to F. I, global view of HIV-1 TAR recognition by the cyclic peptide JB181 (PDB entry 6d2u) (63). The S c value was calculated from the lowest energy NMR structure.…”
Section: Molecular Recognition Of Tar By Tat Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…During the reviewing of this work, two interesting papers were published that could help the design of an effective TAR binder. In particular, Schulze-Gahmen and Hurley solved the crystal structure of the TAR in complex with Tat and the SEC core (CycT1/CDK9/AFF4) [43], while Varani and co-workers reported the NMR structure of TAR RNA in complex with a ultra-potent macrocyclic peptide that mimics the Arginine Rich Motif (ARM) of Tat [44], which however only weakly inhibit the Tat-mediated transcription.…”
Section: Resultsmentioning
confidence: 99%